Hierarchical CoMoO4 nanoneedle electrodes for advanced supercapacitors and electrocatalytic oxygen evolution. (1st January 2018) - Fang, Linxia; Wang, Fan; Zhai, Tianli; Qiu, Yan; Lan, Mengdi; Huang, Kejing; Jing, Qiangshan
Abstract: A novel hierarchical architecture of CoMoO4 nanoneedle with high electrochemical performance was synthesized using a facile one-step hydrothermal method. As the active electrode material in supercapacitors, it exhibited a large specific capacitance (1628.1 C g −1  at a current density of 2 mA cm −2 ), a high rate capability (874.8 C g −1  at 50 mA cm −2 ), and superior cycling stability (90.54% capability retention after 5000 cycles at 10 mA cm −2 ). Moreover, as an electrocatalyst for the oxygen evolution reaction (OER), the CoMoO4 nanoneedle exhibited an early onset potential of 1.37 V, a small Tafel slope of 66 mV Dec −1, and a low overpotential of 235 mV at the current density of 10 mA cm −2 . The excellent electrochemical performance of the hierarchical CoMoO4 structure was attributed to its porosity and the characteristics of the 2D nanosheet subunits that possess many active reaction sites, rapid electron/ion transport, and high stability. The synthetic strategy used in the present study is simple, cost-effective, and generalizable. It can be used to develop effective electrode materials for large-scale energy storage and conversion applications. Highlights: A hierarchical CoMoO4 nanoarchitecture was synthesized. The novel nanoarchitecture was constructed by CoMoO4 nanoneedle subunit. The hierarchical CoMoO4 manifests multi-functional electrochemical performances. They deliver excellent supercapacitor performance. They exhibit remarkable electrocatalytic activity to OER.